Implementation of wireless sensor network (WSN) on garbage transport warning information system using GSM module. (March 2019) - Satria, Dedi; Zulfan; Munawir; Hidayat, Taufik
Abstract: The waste transport transportation system currently running is still using a scheduling system that prioritizes scheduled routes or locations. From the current system, it can be seen that there are still places that have accumulation of garbage. Therefore, a waste warning information system is needed that can provide information on the accumulation of garbage that must be transported immediately. Based on these problems, the purpose of this article is to discuss the creation of a prototype of a waste transport warning system by applying the Wireless Sensor Network (WSN) system using GSM communication media. The client system prototype is built using an ultrasonic sensor that is used as a full garbage detector, Arduino Uno microcontroller, GSM module. Whereas in the information system server system warning waste transport uses the mySQL, PHP and Gammu databases. ) From the test results it is found that the client system has been able to send garbage data in full condition to the information system server. And the server has been able to display the results of sending data in the form of web pages. Next from the waste transport warning information system page, the operator can send the full location data of the garbage to be immediately transported to the transporting officer in the form of an SMS.